Warisan Budaya dan Adaptasi Sosial: Internalisasi Nilai-Nilai Paddisengeng oleh Etnis Bugis-Bone di Desa Masamba - Rusman, Rusman; Junaidi, M.; Hidayat, Rahmat; Badollahi, Muh. Zainuddin; Hapsa, Hapsa (CV. Social Politic Genius (SIGn), 2023)
This research aims to understand the processes and effects of internalizing paddisengeng values by the Bugis-Bone ethnicity residing in Masamba Village. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the process of internalizing paddisengeng values by the Bugis-Bone ethnicity in Masamba Village, which includes the stages of introduction and understanding as well as acceptance and integration, has successfully instilled values such as compassion, honesty, integrity, honor, decorum, hard work, migration, and religious morality. However, the internalization has also presented challenges, particularly regarding the shift in siri’ values that may encourage ostentatious and vanity behavior, potentially reducing social coherence. Therefore, it is recommended that the Department of Education and Culture of Poso Regency, parents, and the Bugis-Bone ethnicity in Masamba Village continue nurturing and developing the practice of internalizing paddisengeng values. The Department of Education and Culture can support this initiative through educational programs that integrate cultural values into the school curriculum and cultural activities that raise awareness of the importance of these values for the younger generation. Parents are advised to continue teaching their children these values in ways relevant to modern life, emphasizing the importance of hard work, honesty, and integrity without losing the true essence of siri’ values. The Bugis-Bone ethnicity needs to maintain constructive intergenerational dialogue to ensure that these values are preserved and creatively adapted to face the challenges of the times. Through this collaborative approach, paddisengeng values are expected to continue serving as a strong foundation for the Bugis-Bone ethnicity in Masamba Village, enriching their cultural heritage while remaining responsive and adaptive to social changes.